Rethinking the Alienation of African Indigenous Languages in African literature: A Post-colonial perspective - Montle, Malesela Edward (Technium Social Sciences Journal, 2021)
The emergence of European forces in Africa between the 1870s and 1900 marked the threshold of a new African identity moulded by Western ideologies. This resulted in the shift of identities and instigation of maladies that spread from the colonial period to the post-colonial era. These ills that are inspired by the colonial past, among other things, threaten the social and political emancipation of Africa and her people in the post-colonial dispensation. Therefore, this is qualitative paper aimed to rethink the degree of destruction that the colonial legacies pose to the Post-colonial Africa with a special attention paid to the alienation of African indigenous languages in African literature. The paper is theoretical in nature and employs the post-colonial theory and its strand, Afrocentricity as a grounding to explore the limitation of African indigenous languages in African literature. Western-originated languages such as English, French and Portuguese are still being widely used across the African continent in the post-colonial period and seem to domineer the space of African literature. This is done at the expense of African indigenous languages, which continue to be marginalised by colonial influence. The study concludes that African literature is expressed and embraced in Western-originated languages than African indigenous languages and this engenders identity-crisis.